2019
DOI: 10.1007/s11085-019-09886-1
|View full text |Cite
|
Sign up to set email alerts
|

Transformation and Precipitation Processes in a Metal Substrate of Oxidized TiAl-Based Alloys

Abstract: This paper presents research results on the oxidation of γ-TiAl-based alloys collected over many years. The oxidation exposures were carried out in air at 875-975 °C. Micro-areas close to the interface of the oxidation product-metallic substrate were analyzed. It was shown that the oxidation process takes place as a result of the outward diffusion of titanium ions, aluminum and alloying elements as well as the inward diffusion of oxygen and nitrogen, and the course of oxidation was also determined by the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…This means diffusion of O towards the bulk and of Al towards the surface. This observation is in agreement with the usual description of the phase sequence in the sub-surface of oxidized TiAl, namely: TiAl -Al depleted zone -TiO2+Al2O3 [3,4]. Concerning Al, an estimatio n of the diffusion length d can be carried out using the usual relation = 2√ (with D: self diffusion coefficient and t: time).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This means diffusion of O towards the bulk and of Al towards the surface. This observation is in agreement with the usual description of the phase sequence in the sub-surface of oxidized TiAl, namely: TiAl -Al depleted zone -TiO2+Al2O3 [3,4]. Concerning Al, an estimatio n of the diffusion length d can be carried out using the usual relation = 2√ (with D: self diffusion coefficient and t: time).…”
Section: Discussionsupporting
confidence: 86%
“…A review can be found for example in Appel's book [1]. Oxidation processes of TiAl give rise to the following phase sequence in the sub-surface: TiAl -Al depleted zone -TiO2+Al2O3 [3,4]. The Nb and Mo elements which are added to the TNM-B1 alloy have been found to improve oxidation resistance [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The observed rates indicate that the oxidation is mainly dominated by bulk diffusion. In particular, Maleka [18] has recently shown that the oxidation process takes place as a result of the outward diffusion of titanium and aluminium, as well as the inward diffusion of oxygen. Therefore, for a complete understanding of the oxidation mechanisms, the knowledge of the diffusion coefficients of all the species involved in the process is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…As compared to B characterized with a solubility of <1 at%, [ 49 ] the extensive solubility of N in the α‐phase (up to 23 at%) results in the formation of a solid solution via interstitial diffusion. [ 50 ] The diffusion of N atoms into the interstitial sites of Ti has been reported to result in the expansion of the α‐Ti crystal lattice, causing compressive strains. [ 51 ] Therefore, it is deduced that the induced lattice expansion is responsible for the peak shifts observed in Figure 2b.…”
Section: Resultsmentioning
confidence: 99%